Psychometric Properties of Scales for Assessing the Vision-related Quality of Life of People with Low Vision: A Systematic Review (2023)
ABSTRACT: Objective: To synthesize information on the psychometric properties of scales used to assess vision-related quality of life in people with low vision. Methods: A systematic review was conducted. The Cochrane Library, Embase, PubMed, Bireme and Epistemonikos databases were consulted in July 2020. Eligibility assessment of abstracts and full texts was performed independently by two investigators.A standardized template was used for data extraction regarding study design, scale and version, clinical condition of participants, and psychometric properties measured, using database-specific controlled vocabulary terms for low vision and keywords for vision-related quality of life and validity. Data was synthesized considering two approaches for scales validations, Classical Test Theory and Rasch Analysis. Results: A total of 53 articles were included in our analysis. In total, 40 studies evaluated the NEI VFQ scale, four evaluated the IVI scale, two evaluated the VA LV VFQ instrument and seven validated the LVQOL scale. This review found that the VRQoL NEI VFQ, IVI, LVQOL and VA LV VFQ-48 scales have adequate psychometric properties, with good internal consistency, when assessed using the CTT approach. The NEI VFQ scale also showed adequate test-retest reliability and adequate construct and content validity. The NEI VFQ and LVQOL scales showed inadequate items and multidimensionality when Rasch analysis was used. The IVI scale showed potential for assessing change in HRQoL after providing interventions to patients with low vision. Conclusions: Many questionnaires exist to measure vision-related quality of life in people with low vision, but the psychometric properties of the questionnaires are variable. Keywords: IVI; LVQOL; Low vision; NEI VFQ; VA LV VFQ-48; reliability; validity; vision-related quality of life.